Client-Centered Business Consulting The Power of Psychological Understanding - Addimando, Federico (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book explores the psychology behind effective business consulting. We dive into the various factors that shape client behavior and decision-making, and we provide insights into the most effective techniques and strategies for building rapport, establishing trust, and delivering value. Whether you are a seasoned consultant looking to refine your skills, or a new consultant seeking to build a solid foundation, this book is designed to provide you with the tools and knowledge you need to succeed in the dynamic and demanding world of business consulting.
Chapter 1. Becoming a Business Consultant -- Chapter 2. Understanding the Client -- Chapter 3. Finding New Clients -- Chapter 4. Approaching the Client -- Chapter 5. Consulting Best Practices -- Chapter 6. How to set the right price -- Chapter 7. Practical Advice for Effective Consultation.
Keywords: Psychology, Industrial; Consumer behavior; Industrial Psychology; Organizational Psychology; Consumer Behavior .